Well Integrity for Workovers and Recompletions - Skinner, Les; Skinner, Les (Gulf Professional Publishing, 2021)
Well Integrity for Workovers and Recompletions delivers the concise steps and processes necessary to ensure that production wells minimize failure. After understanding the introductory background on well integrity and establishing the best baseline, the reference advances into various failure modes that can be expected. Rounding out with an explanation and tools concerning economic considerations, such as how to increase reserve potential and rate of return, the book gives oil and gas engineers and managers a vital solution to keeping their assets safe and effective for the long-term gain. - Helps readers understand how to protect wells through the production, workover and recompletion lifecycle, both from an economic standpoint and technical view - Includes real-world examples with quizzes included at the end of each chapter - Examines why establishing an integrity baseline is important, along with a Well Integrity Management System